ChemInform Abstract: Catalytic Asymmetric Synthesis of Allylic Alcohols and Derivatives and Their Applications in Organic Synthesis. Issue 29 (1st July 2013) - Lumbroso, Alexandre; Cooke, Michael L.; Breit, Bernhard
Abstract: Review: ca. 570 refs.